History of Rationalities Ways of Thinking from Vico to Hacking and Beyond - Sciortino, Luca. (Cham : Springer Nature Switzerland : Imprint: Palgrave Macmillan, 2023)
Over time, philosophers and historians of science have introduced different notions of 'ways of thinking'. This book presents, compares, and contrasts these different notions. It focuses primarily on Ian Hacking's idea of 'style of reasoning' in order to assess and develop it into a more systematic theory of scientific thought, arguing that Hacking's theory implies epistemic relativism. Luca Sciortino also discusses the implications of Hacking's ideas for the study of the problem of contingency and inevitability in the development of scientific knowledge.
Chapter 1: A brief history of the concept of 'ways of thinking': introduction and plan of work -- Chapter 2: Notions of the concept of 'ways of thinking': from classical historical epistemology to Kuhn -- Chapter 3: Notions of the concept of 'ways of thinking': from Hacking to Daston and Galison -- Chapter 4: Taxonomy of the notions of the concept of 'ways of thinking' -- Chapter 5: Developing the styles project: towards a 'theory of styles of reasoning' -- Chapter 6: Styles of reasoning and relativism -- Chapter 7: The incommensurability of styles of reasoning: the case of the existence of theoretical entities -- Chapter 8: Styles of reasoning, contingency and the evolution of science -- Chapter 9: Epilogue.
Keywords: Intellectual life -- History; Science -- History; Knowledge, Theory of; Science -- Philosophy; History of Ideas; Intellectual History; History of Science; Epistemology; Philosophy of Science